Reflexos do discurso da privatização sobre os empregados públicos - Araujo, Gilberto Lima (2020)
Introduction: Brazil, as well as in a good part of the world, is going through a serious economic crisis causing reflections in the traditional employment model, governed by a formal contract that defines non-casual work relations with the receipt of compensation through a fixed salary that is passing due to transformations, which tend not to return to the point of origin due to the fact that in the national territory we have more than four hundred public companies and in view of the aforementioned crisis, the federal government found itself obliged to seek strategies to raise resources and reduce costs, one of which was a privatization program is underway that provides for the sale of many state-owned companies. The problem: The privatization of Public Companies also involves a Public Management strategy for its human resources as they are disconnected from the public service during the process in a mandatory and unprepared manner and even though one of the consequences of privatization is the high rate of subsequent dismissals. , and we did not observe in the privatization program strategies aimed at the employees of these public companies. When the government speaks that it intends to privatize all Public Companies, we are talking about a population of public employees of more than eight hundred thousand people. Thus, it was found justification for the research in dealing with a Federal Government Public Management strategy, combating unemployment and its effects being a challenge to governments and still dealing with the interest of almost five hundred thousand federal public employees. Thus, the main objective is to identify the consequences of the privatization discourse on employees of a federal public company. In theoretical terms, fundamentals are used on Indirect Administration, especially the Public Company and its personnel regime, on Employment and Professional Careers, Stability and the reflex of privatization, Privatization and Postal Services. As for the methods and procedures, the qualitative, diagnostic approach was used, configuring the research as exploratory-descriptive. Data collection took place through a focus group with administrative employees and semi-structured individual interviews with agency managers, carried out outside the workplace and the company, all with public employees from the Southern Regional Service Management of the Espírito Santo State Superintendence. studied company and also through observation. As a result, having obtained the results, it was possible to show that before privatization there is already a feeling of loss of labor benefits in the employee and also the fear of loss of employment and of more benefits if privatization actually occurs. It was reported that the privatization discourse has had an impact on the psychological aspects of the employee and his family and the employees' indignation due to uncertainty, due to the lack of official information about the employee in the process. From the results, as a technical product, the project was elaborated: Technical report: preliminary project containing the impacts caused by the privatization discourse on public employees and with suggestions for actions aimed at minimizing them.